Peningkatan Motivasi dan Hasil Belajar IPS Materi Perubahan Sosial dan Budaya Melalui Penerapan Model Pembelajaran Problem Based Learning di MTs Negeri 4 Bantul - Wuryantini, Wuryantini (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to improve motivation and learning outcomes through a problem-based learning model in social studies subjects. This research is class action research carried out in 2 cycles with two meetings in each cycle. The subjects of this study were students of class IX-A MTs Negeri 4 Bantul. The stages in this study include planning, implementation, observation and reflection. The data collection technique carried out is to use questionnaires and observation guidelines. Data analysis techniques use quantitative descriptive methods. The results showed that with the application of the Problem Based Learning model, motivation and learning outcomes of students can be improved. In cycle I the increase in student motivation increased by 78.57% to 92.85% in cycle II. The increase in learning outcomes is evidenced by an increase in the number of students who obtained scores above KKM, namely in cycle I by 64.28%, increasing to 89.28% in cycle II from a total of 28 students.